THE EFFECTIVENESS OF SISTER CITY PROGRAM OF SEMARANG – BRISBANE - Mohammad Fikri Haikal (HI 15 UMY 066, 2015)
*66 The sister city program of Semarang – Brisbane have been quite long journey. It was started in 11 January 1993 as continuing the program of sister province between Central Java and Queensland (Australia). The cooperation had experienced of 2 (two) extended of Memorandum of Understanding (MoU). The first period was on 11 January 1998 and the second period on 09 September 2002. In the MoU agreement, many fields had become programs of both cities. Those are on agriculture, urban and environmental development, transportation and tourism, industry and handicrafts, trade and investment, education, science and technology, art and culture. On 24 October 2013, Griffith University (Brisbane) and the government of Semarang city signed the MoU that covered many fields too which are special on educational sectors. To explain this topic, the writer used descriptive method. It means by describing, explaining subject or object based on the data where the research began from general things, explained by collecting, arranging, and interpreting data based on this undergraduate thesis classification. The data collecting technique used library research by various sources such as book, journal, document, newspaper, archive and site (internet). Beside that, to look for other information related to the topic, the writer also interviewed with some informants. Public Policy theory is becoming reference which is in the aspect of evaluation in order to elaborate the topic. The result of research shows that this sister city program of Semarang - Brisbane is not optimal enough. Most of field programs are not running well, because it faced many obstacles either in the aspect of bureaucracy (un-capable) or even in the mayor aggressiveness not so serious. Overall the program implementations are still not in hope, but in the mutual relationship it can be appreciated which can hold 22 years. On July 2015, there will be the third of MoU extended, of course by new evaluation and new program that match with the need of both cities. hence, better quality of sister city program will be got nicely in the future